Amony 2015. I am Evelyn Amony - Mlambo, Obert (AAeO - Afrikanistik-Aegyptologie-Online, 2017)
Evelyn Amony 2015. I am Evelyn Amony: Reclaiming my Life from the Lord’s Resistence Army. Madison: The University of Wisconsin Press, ISBN978-0-299-30494-2, 26,95.